INFLUENCE OF HERBICIDES ON MORPHO-PHYSIOLOGICAL GROWTH PARAMETERS IN TURMERIC (CURCUMA LONGA L.) - B. B. CHANNAPPAGOUDAR,; V. BABU,; B. NAGANAGOUDAR,; RATHOD, SANTOSHA (The Bioscan, 2013)
To study the influence of different herbicides on growth and growth parameters in turmeric with and without weeds and their influence on rhizome yield field studies were under taken at Main Agricultural Research Station, University of Agricultural Sciences Dharwad during kharif 2009-10. Result indicated that the efficacy of different herbicides was significant. Weed free check recorded higher values of all the morpho-physiological growth parameters in turmeric. Among the herbicides pre-emergence application of pendimethalin @1.5 kg a.i. ha-1 and 1.0 kg a.i. ha-1 recorded higher values of growth parameters. Weed free check and pendimethalin @ 1.5 kg ha-1 had higher weed control efficiency and higher growth values of LAI, LAD, AGR, CGR and NAR as compared to unweeded control. Higher growth values in weed free check and pendimethalin @ 1.5kg ha-1 increased the rhizome yield as against unweeded control.